Dead fall - Mehl, Nancy (Mehl, Nancy. Quantico files ;, 2021)
"When a renowned profiler is found dead in his hotel room and it becomes clear the killer is targeting agents in Alex Donovan's unit, she is called to work on the strangest case she's ever faced. Things get personal when the brilliant killer strikes close to home, and Alex will do anything to find the killer--even at the risk of her own life"--